2008
DOI: 10.1093/occmed/kqm136
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal symptoms among seafood production workers in North Norway

Abstract: Musculoskeletal symptoms were found among the majority of production workers in the whitefish, shrimp and salmon industry, the highest prevalence being among female workers. The main difference between types of seafood industries was the high prevalence of symptoms from wrist/hands among workers in the salmon industry. Cold work was an important risk factor for musculoskeletal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
4
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 17 publications
5
51
4
2
Order By: Relevance
“…The body region locations of the WRMSDs are concomitant to the usual postures/or risk factors associated with butchering. Generally, upper limbs WRMSDs in the present study were not as dominant as those reported by previous studies [32], [33], [34]. This could be attributed to differences in work settings between our study and those of the comparison studies.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…The body region locations of the WRMSDs are concomitant to the usual postures/or risk factors associated with butchering. Generally, upper limbs WRMSDs in the present study were not as dominant as those reported by previous studies [32], [33], [34]. This could be attributed to differences in work settings between our study and those of the comparison studies.…”
Section: Discussioncontrasting
confidence: 74%
“…Most slaughterhouses in the developed world maintain low temperature for hygiene purposes. This temperature regulation has, however, been linked to preponderance of upper limb WRMSDs [32], [33], [34]. Direct comparison cannot be made with these studies for two reasons.…”
Section: Discussionmentioning
confidence: 90%
“…As principais formas de LER/DORT diagnosticadas no citado ambulatório foram: tenossionovites e tendinites, síndrome do túnel do carpo e síndrome cérvico-braquial. Estas alterações já são relatadas em estudos sobre a pesca industrial, a exemplo de Olafsdottir (1998) e Aasmoe et al (2008).…”
Section: Riscos E a Visatunclassified
“…Many processing jobs involve repetitive and vigorous motions, extended periods of time standing, heavy lifting and awkward postures. A fast paced environment is also typical of the industry [21,32,33]. Musculoskeletal disorders affecting the neck, shoulders, back and upper and lower limbs with disorder prevalence and severity correlated with particular worker tasks have been documented [34][35][36].…”
Section: Feed Mills Processing Plantsmentioning
confidence: 99%